Animasi Sinematik Dinosaurus Secara 3D Menggunakan Blender dengan Metode Pose to Pose - Putra Dama Ramadhan; Agung Triayudi; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
Dino Park, located in East Java, is a tourist attraction that uses the concept of dinosaurs as the main attraction. Dinosaurs themselves lived approximately 200 million years ago in the Jurassic period. In helping to increase visitors at Dino Park, promotional media is needed to promote dinosaur tourism. Making animation for this promotion using blender software version 3.4. Blender is a software that offers full functionality for modeling, texturing, rigging, animating, and rendering. Cinematic animation has become a powerful tool to produce visual works that can attract audiences in today's digital age. This abstract explores aspects of cinematic animation in the context of using blender. The character creation process includes 3D models, textures to give a sense of life to the model, scene-setting techniques that include lighting, and camera placement to produce an immersive atmosphere. In this research, the author uses the pose to pose method to produce a cinematic 3D promotional animation with good motion. This method aims to simplify planning, improve animation quality and make it easy to correct flaws in the animation. The pose to pose method in cinematic animation has become a powerful approach in creating stunning visual experiences. It provides precise control and unlimited creativity in character movement, allowing animators to create 3D animations with smoother and more natural-looking animated movements